Attitudes and preferences towards palliative and end of life care in patients with advanced illness and their family caregivers in Latin America: A mixed studies systematic review. (September 2021) - Dittborn, Mariana; Turrillas, Pamela; Maddocks, Matthew; Leniz, Javiera
Background: Achieving universal access to palliative care is considered a global and equity priority. Understanding patients and caregivers' attitudes and preferences towards palliative and end-of-life care in Latin America is essential to develop person-centred services in the region. Aim: To synthesize and appraise the evidence about patients with advanced illness and their caregivers' attitudes and preferences towards palliative and end-of-life care in Latin America. Design: Mixed studies systematic review with sequential exploratory synthesis (thematic and narrative synthesis). Quality was assessed using the Mixed-Methods Appraisal Tool. Data sources: MEDLINE, Embase, PsychINFO, Lilacs, Web of Science, Scielo and Scopus to March 2021. Empirical studies examining patient or caregiver attitudes and/or preferences towards palliative and end-of-life care were included. Results: Of 3575 records screened, 45 articles were included, comprising 7 countries and a total of 1220 patients and 965 caregivers (26.8% non-cancer-related participants). Data were organized around seven themes: Symptom management and nutrition; End-of-life medical decisions; Communication patterns; Place of end-of-life care and death; God and religious community as source of hope and support; Caregiver's role; and Mixed understandings of palliative care. Main findings include; conflicted views around palliative care and pain relief; patients' preference to be informed about their condition contrasting with caregivers' reluctance to discuss this with patients; common preference for shared decision-making; and overburdened caregivers lacking professional home-care support. Methodological flaws were found in general. Conclusion: Core themes provide context-specific evidence to inform the design of culturally sensitive palliative and end-of-life care services, models and public policies in Latin America.